Activation of epidermal growth factor receptor/insulin-like growth factor 1 receptor-β-Catenin-CD44 pathway in periampullary cancer - Bankura, Biswabandhu; Maji, Suvendu; Chakraborty, Balarko; Alam, Neyaz; Panda, Chinmay (Journal of Radiation and Cancer Research, 2020)
Background: Periampullary cancer (PC) is a global medical burden. Less than 5% of patients experience an overall survival of 5 years or more. The study aims to analyze the importance of epidermal growth factor receptor (EGFR)/insulin-like growth factor 1 receptor (IGF1R)-beta-catenin (β-catenin)-CD44 pathway in the development of periampullary cancer of Indian patients. Subjects and Methods: Expression profile of EGFR, IGF1R, β-catenin, and CD44 was verified by immunohistochemical analysis in primary tumor samples (N = 14) and respective adjacent normal tissues. Results: In periampullary carcinoma patients, a high level of EGFR expression was seen in 64% of the samples along with co-expression of IGF1R in 77.8% of samples. Furthermore, the high expression of EGFR and IGF1R significantly correlated with the increased expression of β-catenin along with CD44 expression of the tumors. Conclusion: The EGFR/IGF1R-β-catenin-CD44 pathway seems to be important in the development of PC with clinical importance.